1994
DOI: 10.3758/bf03206732
|View full text |Cite
|
Sign up to set email alerts
|

Text-contingent color aftereffects: A reexamination

Abstract: Five experiments reexamined color aftereffects contingent on the semantic properties of text (Allan, Siegel, Collins, & MacQueen, 1989). The influence of different assessment techniques and the effect of eye movements and overlapping contour information on the induction of color aftereffects by word and nonword letter strings were determined. Experiment 1 showed that no aftereffect was found when a traditional method of assessing color aftereffects was used. Experiments 2 and 4 demonstrated color aftereffects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…If the retinal location or spatial frequency is changed between induction and testing, the aftereffect is considerably weakened or absent, depending upon the magnitude of the change (e.g., Harris, 1980;Humphrey, Herbert, Symons, & Kara, 1994;Humphrey, Skowbo, Symons, Herbert, & Grant, 1994;Lovegrove & Over, 1972;Stromeyer, 1972a,b). In short, the McCollough effect does not show translational invariance or size constancy.…”
mentioning
confidence: 99%
“…If the retinal location or spatial frequency is changed between induction and testing, the aftereffect is considerably weakened or absent, depending upon the magnitude of the change (e.g., Harris, 1980;Humphrey, Herbert, Symons, & Kara, 1994;Humphrey, Skowbo, Symons, Herbert, & Grant, 1994;Lovegrove & Over, 1972;Stromeyer, 1972a,b). In short, the McCollough effect does not show translational invariance or size constancy.…”
mentioning
confidence: 99%
“…In another experiment, Stromeyer (1972) found that the ME weakened or disappeared when a test grating was moved to a different retinal area from the induced area. Results of other experiments also indicate that the ME is retinotopic (Broerse & Grimbeek, 1994;Broerse & O'Shea, 1995;Humphrey, Herbert, Symons, & Kara, 1994;Humphrey, Skowbo, Symons, Herbert, & Grant, 1994; for review, see Humphrey, 1998;, but and Siegel, Allan, & Eissenberg (1992 have presented results suggesting that the ME is spatiotopic. It appears that much of the evidence favors a retinotopic account of the ME, but there is certainly room for more research to decide this issue definitely.…”
Section: Discussionmentioning
confidence: 92%
“…Advocates of the conditioning explanation (Allan & Siegel, 1997b;Siegel, Allan, & Eissenberg, 1994) agree that induction with strict fixation will produce CAEs interpretable in terms oflocal (retinotopic) factors, but they contend that CAEs dependent on global (spatiotopic) factors can be obtained with nonfixating subjects. A similar controversy over CAEs contingent on text (Allan, Siegel, Collins, & MacQueen, 1989;Humphrey, Skowbo, Symons, Herbert, & Grant, 1994) also remains unresolved.…”
Section: Theoretical Importancementioning
confidence: 99%